2004
DOI: 10.1073/pnas.0403532101
|View full text |Cite
|
Sign up to set email alerts
|

Methionine sulfoxide reductase A is important for lens cell viability and resistance to oxidative stress

Abstract: Age-related cataract, an opacity of the eye lens, is the leading cause of visual impairment in the elderly, the etiology of which is related to oxidative stress damage. Oxidation of methionine to methionine sulfoxide is a major oxidative stress product that reaches levels as high as 60% in cataract while being essentially absent from clear lenses. Methionine oxidation results in loss of protein function that can be reversed through the action of methionine sulfoxide reductase A (MsrA), which is implicated in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
135
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 164 publications
(144 citation statements)
references
References 53 publications
9
135
0
Order By: Relevance
“…This result agrees with previous data showing that MsrA protects against cell death elicited by other oxidative insults [20][21][22][23]. Evidence suggests that aggresome formation (coupled with autophagy) is a protective mechanism initiated by the cell to eliminate misfolded proteins with a high propensity to form toxic aggregates [16,40].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result agrees with previous data showing that MsrA protects against cell death elicited by other oxidative insults [20][21][22][23]. Evidence suggests that aggresome formation (coupled with autophagy) is a protective mechanism initiated by the cell to eliminate misfolded proteins with a high propensity to form toxic aggregates [16,40].…”
Section: Discussionsupporting
confidence: 93%
“…MsrA is present throughout the brain, including the substantia nigra [19]. Cells with increased or decreased levels of MsrA are relatively resistant or vulnerable to oxidative insults, respectively [18,[20][21][22][23]. MsrA protects cells from oxidative stress not only by repairing proteins damaged by methionine oxidation, but also by engaging in a cycle of methionine oxidation and reduction that ultimately results in ROS scavenging [18,22].…”
mentioning
confidence: 99%
“…Kantorow et al (2004) localized MsrA to all regions of the human lens and demonstrated that overexpression of MsrA in lens epithelial cells could protect against H 2 O 2 mediated oxidative stress. Silencing of the MsrA gene using siRNA increased sensitivity to H 2 O 2 mediated oxidative stress in lens cells, interestingly the decrease in MsrA levels lead to decreased viability even in the absence of oxidative stress.…”
Section: The Methionine Sulfoxide Reductase Repair Systemmentioning
confidence: 99%
“…Double-stranded siRNAs specific for MsrA were obtained as previously described (Kantorow et al, 2004). HLE cells were transfected using the Transmessenger Transfection Reagent Kit (Qiagen, Valencia, CA).…”
Section: Short Interfering Rna (Sirna)-targeted Gene Silencingmentioning
confidence: 99%
“…Msr activity has been detected in the human lens (Spector et al, 1982) and both MsrA (Kantorow et al, 2004) and MsrB (Marchetti et al, 2005) are required for protection of lens cells against oxidative stress induced lethality. Of the many systems that can defend the lens against oxidative stress damage, many are localized to the mitochondria suggesting that protection or repair of mitochondrial components is important for lens maintenance.…”
Section: Introductionmentioning
confidence: 99%